Development of Learning Media Using the Smart Apps Creator Application on Human Respiratory System Material of Science for Class V Elementary School - Wahyuni, Ayu; Hendri, Nofri; Eldarni, Eldarni; Supendra, Dedi (Lembaga Penelitian dan Pendidikan Mandala, 2023)
This research aims to produce learning media in accordance with development procedures using standard criteria of validity and practicality so that it becomes a learning media that is suitable for use in the learning process. The type and method of this research is development research or better known as Research and Development (R&D) , using a 4-D development model. The development procedure in this research consists of 4 stages, namely; (1) Define, (2) Design, (3) Develop, (4) Disseminate. The product validation test was carried out by 3 validators, namely 2 media validators and 1 material validator. Product trials were carried out on 20 class V students of SD Negeri 08 Talao with the aim of finding out the practicality of the product being developed. The results of this research explain that the assessment from media validators was declared